Liposome-encapsulated zoledronate increases inflammatory macrophage population in TNBC tumours - Petruk Nataliia; Sousa Sofia; Croset Martine; Polari Lauri; Zlatev Hristo; Selander Katri; Mönkkönen Jukka; Clézardin Philippe; Määttä Jorma (Elsevier, 2025)
Background: Tumour associated macrophages (TAMs) are important players in breast tumour progression and metastasis. Clinical and preclinical evidence suggests a role for zoledronate (ZOL) in breast cancer metastasis prevention. Further, zoledronate is able to induce inflammatory activation of monocytes and macrophages, which can be favourable in cancer treatments. The inherent bone tropism of zoledronate limits its availability in soft tissues and tumours. In this study we utilised an orthotopic murine breast cancer model to evaluate the possibility to use liposomes (EMP-LIP) to target zoledronate to tumours to modify TAM activation.
Methods: Triple-negative breast cancer 4T1 cells were inoculated in the 4th mammary fat pad of female Balb/c mice. Animals were divided according to the treatment: vehicle, ZOL, EMP-LIP and liposome encapsulated zoledronate (ZOL-LIP). Treatment was done intravenously (with tumour resection) and intraperitoneally (without tumour resection). Tumour growth was followed by bioluminescence in vivo imaging (IVIS) and calliper measurements. Tumour-infiltrating macrophages were assessed by immunohistochemical and immunofluorescence staining. Protein and RNA expression levels of inflammatory transcription factors and cytokines were measured by Western Blotting and Taqman RT-qPCR.
Results: Liposome encapsulated zoledronate (ZOL-LIP) treatment suppressed migration of 4T1 cell in vitro.
Tumour growth and expression of the angiogenic marker CD34 were reduced upon both ZOL and ZOL-LIP treatment in vivo. Long-term ZOL-LIP treatment resulted in shift towards M1-type macrophage polarization, increased CD4 T cell infiltration and activation of NF-κB indicating changes in intratumoural inflammation, whereas ZOL treatment showed similar but non-significant trends. Moreover, ZOL-LIP had a lower bisphosphonate accumulation in bone compared to free ZOL.
Conclusion: Results show that the decreased bisphosphonate accumulation in bone promotes the systemic antitumour effect of ZOL-LIP by increasing inflammatory response in TNBC tumours via M1-type macrophage activation.